Impact of Sanction Shock on Iran's Stock Market Index - Reza Tehrani; Mahmood Mokhtarband; Menal Aboodeh (Journal of Asset Management and Financing)
The imposition of Western economic sanctions against Iran has had varying effects on the country's financial markets, with the capital market being one of the sectors not immune to the shockwaves of these sanctions. Given the pivotal role of sanctions in shaping Iran's economic fluctuations, this study aimed to examine the effects of sanctions on the state of the Iranian capital market using a structural macroeconomic econometric model. Unlike previous research, this study accounted for the non-linear, intensity-dependent nature of the sanctions' impact, rather than assuming a constant effect. The research methodology employed an Auto-Regressive Distributed Lag (ARDL) model, considering datasets with both annual and seasonal frequencies over a 30-year period from 1991 to 2021. The findings of the optimal model indicated that the sanctions index had a negative and statistically significant effect on the behavior of the Iranian capital market.